New Record for Science Salvia margasurica Al-Musawi & Al-Hussaini, (Labiatae) in Iraq - Aseel F. A. Al-Hussaini (Journal of Global Pharma Technology, 2017)
Background: The study covered thirty-three species which grown wildly in Iraq and a comparative study for all kinds of morphological characters were done. Principal Findings: The most stable and important taxonomic characters were pointed out, diagrams, illustrations, scheduals, micrographs were also documented. Stamens, nutlets, basal leaves, bracts, bracteoles, calyces, corollas and their trichomes were very important taxanomic characters. The trichomes were variable in variable species therefore used as a diagnostic characters for the species. Conclusions: New species Salvia margasurica Al-Musawi & Al-Hussaini was suggested to be new record for science.Keywords: Salvia, Morphology, Spec. Nov.